Measurement of the local electron temperature in self-compressed plasma stream - Solyakov, D.G.; Volkova, Yu.Ye.; Garkusha, I.E.; Marchenko, A.K.; Ladygina, M.S.; Staltsov, V.V.; Petrov, Yu.V.; Chebotarev, V.V.; Merenkova, T.M.; Makhlai, V.A.; Yeliseyev, D.V. (Вопросы атомной науки и техники, 2021)
The local electron temperature measurements with the double electric probe in the compression zone are presented. Electric probes make it possible to measure the electron temperature with a reasonably good spatial resolution. Double electric probe application for electron temperature measurements in the dense self-compressed plasma stream is discussed. We have shown experimentally that the electric probe operates in a diffusion regime. Наведено результати вимірювань локальної електронної температури подвійним електричним зондом у зоні стиснення. Електричні зонди дозволяють вимірювати температуру електронів з досить високою просторовою роздільною здатністю. Розглянуто застосування подвійного електричного зонда для вимірювання електронної температури в щільному потоці самостисненої плазми. Експериментально показано, що електричний зонд працює в дифузійному режимі. Представлены результаты измерений локальной электронной температуры двойным электрическим зондом в зоне компрессии. Электрические зонды позволяют измерять температуру электронов с достаточно хорошим пространственным разрешением. Обсуждается применение двойного электрического зонда для измерения электронной температуры в плотном потоке самосжатой плазмы. Экспериментально показано, что электрический зонд работает в диффузионном режиме.